Discovery and SAR of novel series of imidazopyrimidinones and dihydroimidazopyrimidinones as positive allosteric modulators of the metabotropic glutamate receptor 5 (mGlu5). Issue 6 (15th March 2015) - Martín-Martín, María Luz; Bartolomé-Nebreda, José Manuel; Conde-Ceide, Susana; Alonso de Diego, Sergio A.; López, Silvia; Martínez-Viturro, Carlos M.; Tong, Han Min; Lavreysen, Hilde; Macdonald, Gregor J.; Steckler, Thomas; Mackie, Claire; Bridges, Thomas M.; et al.
Graphical abstract: Abstract: We report the discovery and SAR of two novel series of imidazopyrimidinones and dihydroimidazopyrimidinones as metabotropic glutamate receptor 5 (mGlu5 ) positive allosteric modulators (PAMs). Exploration of several structural features in the western and eastern part of the imidazopyrimidinone core and combinations thereof, revealed compound4a as a mGlu5 PAM with good in vitro potency and efficacy, acceptable drug metabolism and pharmacokinetic (DMPK) properties and in vivo efficacy in an amphetamine-based model of psychosis. However, the presence of CNS-mediated adverse effects in preclinical species precluded any further in vivo evaluation.